(untitled) (ModaPalavra e-periódico, 2016)
The printed shirts with philanthropic phrases or social mobilization campaigns, made by high luxury companies or governments, links the citizen in a number of situations where the appearance is much more complex than it seems. The article aims to analyze the philanthropic t-shirts of the american luxury companies which have global influence and t-shirts with prints produced by municipal and state governments of Rio de Janeiro.